Experimental infection with a haemorrhage-causing Trypanosoma vivax in N'Dama and Boran cattle - Williams, D.J.L.; Logan-Henfrey, L.L.; Authié, Edith; Seely, C.; McOdimba, F.A. (Wiley, 1992)
N'Dama cattle control experimental infections with clones of Trypanosoma congolense of varying degrees of virulence, but nothing is known about their capacity to control infections caused by highly virulent. East African stocks of T. vivax. Thus four N'Damas and four trypanosusceptible Borans were infected with a tsetse‐transmitted stock of T. vivax. IL2337. In Ayrshire cattle this stock is known to cause severe haemorrhagic disease.No differences were observed in the parasitaemia between the two groups. Both groups became anaemic. The mean packed cell volume fell to 16.8 ± 5.0% in the N'Dama cattle and to 24.2 ± 2.2% in the Borans on day 26 post infection. These differences were not significant. Antibody responses to invariant trypanosome antigens were analysed. No differences were observed between the groups in the pattern of recognition or the isotype elicited. Antibody bound to the surface of erythrocytes was occasionally detected. No anti‐platelet activity was observed.The results show that N'Dama cattle, which are known to be resistant to disease caused by T. congolense and by T. vivax stocks from West Africa, were highly susceptible to an infection of T. vivax which causes acute haemorrhagic disease.